Teaching reading in large classes (2001)
This article deals with the problem of overcrowded classes. Ideas from research findings are given in an attempt to approach the teaching of reading at tertiary and secondary levels. This study is mainly based on the analysis of five pedagogical principles that emerged from the Lancaster-Leeds Language Learning in Large Classes Research Project in the United Kingdom (1986- 1999). Emphasis is also made on two important general principles emerging from the project: being realistic and giving more responsibility to the learner. Practical suggestions from research on reading are made based on the principles stated.